The Role of Women in Food Security of Fishing Families Amidst Climate Change: A Gender and Poverty Analysis - Sri Wahyuni; Rahma Syafitri; Nanik Rahmawati; Emmy Solina; Yudhanto Satyagraha Adiputra (Lembaga Bale Literasi, 2026)
Coastal fishing communities are highly vulnerable to climate change, as shifting weather patterns disrupt marine livelihoods and destabilize household food security. Seasonal extremes, such as strong winds, high waves, and extended unsafe fishing periods, reduce fishing activity and income, intensifying poverty risks and limiting access to food. Within this fragile socio-ecological context, women in fishing households undertake critical yet often overlooked roles that sustain family resilience. This study examines the central role of fisherwomen in maintaining household food security amid climate-related disruptions. Employing a qualitative approach in Bintan Regency, Riau Islands Province, the research draws on in-depth engagement with fishing households to explore lived experiences, gendered labor divisions, and adaptive strategies shaped by seasonal climate variability. The analysis integrates gender and poverty perspectives to understand how resilience is constructed at the household level. Findings indicate that fisherwomen perform dual roles in both public and domestic spheres. Publicly, they engage in fish processing, petty trade, and other income-generating activities that offset reduced earnings during non-fishing seasons. Domestically, they regulate consumption, diversify food sources, and strategically manage limited resources. Although climate change increases their workload and deepens economic vulnerability, women actively develop anticipatory strategies, such as livelihood diversification, food preservation, and informal support networks, that mitigate food insecurity. This study contributes by repositioning women as central agents in climate adaptation and household food governance, moving beyond male-centered or macro-level analyses of fisheries. The findings highlight the transformative role of women’s everyday practices in sustaining coastal livelihoods and underscore the need for gender-responsive policies that strengthen local adaptive capacities.